Analysis of phase trajectories for studying the operational evolution of catalytic systems - A. F. Schmidt; A. A. Kurokhtina; E. V. Larina; N. A. Lagoda (Тонкие химические технологии)
Objectives. To establish details of catalytic systems operation using the kinetic method with no needs for the differentiation of primary experimental kinetic data.Methods. Analysis of the time patterns of differential selectivity and relative reactivity of substrates in parallel or competing reactions was used.Results. For various coupling reactions of aryl halides and nucleophiles, the possibility to obtain the data about the evolution of the catalytic systems and patterns of the changes of catalytically active species under dynamic transformations of several active and inactive catalyst forms was demonstrated.Conclusions. The analysis of the evolution of differential selectivity and relative reactivity under competing or parallel reactions is the useful tool for discrimination between probable hypotheses of complex catalytic process operation.